Mammalian Tribbles Homologs at the Crossroads of Endoplasmic Reticulum Stress and Mammalian Target of Rapamycin Pathways. (30th December 2013) - Cunard, Robyn
Abstract : In 2000, investigators discovered Tribbles, a Drosophila protein that coordinates morphogenesis by inhibiting mitosis. Further work has delineated Xenopus (Xtrb2), Nematode (Nipi-3), and mammalian homologs of Drosophila tribbles, which include TRB1, TRB2, and TRB3. The sequences of tribbles homologs are highly conserved, and despite their protein kinase structure, to date they have not been shown to have kinase activity. TRB family members play a role in the differentiation of macrophages, lymphocytes, muscle cells, adipocytes, and osteoblasts. TRB isoforms also coordinate a number of critical cellular processes including glucose and lipid metabolism, inflammation, cellular stress, survival, apoptosis, and tumorigenesis. TRB family members modulate multiple complex signaling networks including mitogen activated protein kinase cascades, protein kinase B/AKT signaling, mammalian target of rapamycin, and inflammatory pathways. The following review will discuss metazoan homologs of Drosophila tribbles, their structure, expression patterns, and functions. In particular, we will focus on TRB3 function in the kidney in podocytes. This review will also discuss the key signaling pathways with which tribbles proteins interact and provide a rationale for developing novel therapeutics that exploit these interactions to provide better treatment options for both acute and chronic kidney disease.